2022
DOI: 10.1111/bcpt.13826
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rifampicin on porphyrin metabolism in healthy volunteers

Abstract: Pregnane X receptor (PXR) is known to stimulate haem synthesis, but detailed knowledge on the effects of PXR activation on porphyrin metabolism in humans is lacking. We utilized a randomized, crossover, open (blinded laboratory) and placebo‐controlled trial with 600‐mg rifampicin or placebo dosed for a week to investigate the effects of PXR activation on erythrocyte, plasma, faecal and urine porphyrins. Sixteen healthy volunteers participated on the trial, but the number of volunteers for blood and urine porph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…2 Besides its impact on drug metabolizing enzymes and transporters, early findings by McColl et al 30 showed significantly higher urinary levels of markers for heme biosynthesis after long-term treatment with RIF. Moreover, Tolonen et al 10 reported an effect of multiple doses of RIF on the urinary and fecal porphyrin elimination, but no higher porphyrin levels were observed in plasma. The latter group performed their analysis 1 day after the last RIF administration, suggesting no direct inhibitory effect on OATP1B1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Besides its impact on drug metabolizing enzymes and transporters, early findings by McColl et al 30 showed significantly higher urinary levels of markers for heme biosynthesis after long-term treatment with RIF. Moreover, Tolonen et al 10 reported an effect of multiple doses of RIF on the urinary and fecal porphyrin elimination, but no higher porphyrin levels were observed in plasma. The latter group performed their analysis 1 day after the last RIF administration, suggesting no direct inhibitory effect on OATP1B1.…”
Section: Discussionmentioning
confidence: 99%
“…8 In the same preclinical model, no influence on CP levels was observed in the period after a long-term treatment with RIF. 9 In humans, Tolonen et al 10 reported increased urinary CPI levels after 7-day RIF treatment. Unfortunately, their study was not designed to determine the corresponding blood CPI levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation